Issues of public health and involvement in mass sports - Jamilov Shohruz (Genius Publishing Group, 2022)
This article describes the effects of exercise on the human body and on improving the health of the population and creating opportunities for them to engage in regular sports.
Keywords: Coronavirus infection; proper nutrition; skill; physical activity